History of Scientific Contacts between Russian and French Plant Physiologists in the Late ХIХ Century - 1970s - Mariya V. Malunova (RUDN Journal of Russian History)
The author has investigated the history of scientific relations and cooperation between Russian and Soviet scientists in the field of plant physiology with their French colleagues in the period from the end of the XIX century to the 1970s. The authors consider the changes that took place in the relations between scientific communities after the Great Russian Revolution of 1917, between the two world wars, and the beginning of the Cold War. The specific areas of cooperation between the scientists, the problems that aroused the greatest interest of plant physiologists of the two countries are reflected upon in the article. Through the article there is an analysis of the development of scientific ties with the help of scientific trips of plant physiologists to France and the USSR, which became, on the one hand, an important part of scientific diplomacy, and on the other hand, a factor that allowed a new impetus to the development of science in the two states.